Parallel programming with MPI - Pacheco, Peter S.
A hands-on introduction to parallel programming based on the Message-Passing Interface (MPI) standard, the de-facto industry standard adopted by major vendors of commercial parallel systems. This textbook/tutorial, based on the C language, contains many fully-developed examples and exercises. The complete source code for the examples is available in both C and Fortran 77. Students and professionals will find that the portability of MPI, combined with a thorough grounding in parallel programming principles, will allow them to program any parallel system, from a network of workstations to a parallel supercomputer.